Teknologi 3D dalam Proses Pembuatan Komik - Permadi, Johanes Baptista (Humaniora, 2011)
Comic has been people?s favorite since 1930. As the growth of years and technology, the demands in designing comic were also increasing. To fulfill the demands, comic authors spent their times to draw so that they have no time to discover other element besides technical. Therefore, it is important if the comic author helped by 3D technology to accelerate technical process so that the comic authors will get extra time to develop other elements like concept and story. Data is gathered from interviews with both semi-professional and professional comic authors who are having problems being solved. Solving problems are conducted by using 3D software to draw picture of distorted space. And then two semi-professional comic authors will try to draw distorted space in tracing the picture from 3D software to see how many times needed to draw hard part traditionally.